An Economic Analysis of Intellectual Property Rights Infringement Field Studies in Developing Countries - Domon, Koji (Palgrave Studies in Institutions, Economics and Law,, 2018)
Using unique field research from across Asia, this book examines the real markets of illicit products that breach intellectual property rights (IPR). The text presents three case studies regarding IPR infringements: unauthorised music content; fake spare parts of motorcycles; and fake Japanese food. Each study has unique characteristics, though their general concepts and problems have similar roots. The book shows what is happening in the black market and systems of illicit trade, providing information for stakeholders in Intellectual Property Rights to consider in devising effective methods for minimizing profits lost to copied and fake products.